RISK OF ANEMIA AMONG ELEMENTARY SCHOOL STUDENTS IN EAST KALIMANTAN PROVINCE, INDONESIA: A CASE CONTROL PROTOCOL STUDY - Nugroho, Purwo Setiyo; Sunarti, Sri; Amalia, Nida; Tianingrum, Niken Agus; Kurniasari, Lia; Winarti, Yuliani; Febriyanto, Kresna; Oktaviani, Oktaviani; Susanti, Erni Wingki; Rahman, Ferry Fadzlul; Ghozali, Ghozali; Rachman, Ainur (Krafon Publishing, 2019)
The issue of anemia in Indonesia still remains a homework for the Ministry of Health, as well as other related sectors. According to data from the Basic Health Research (Riset Kesehatan Dasar) in 2013, there are 31% female adolescents in Indonesia who suffers from anemia. However, this number increased to 48.9% according to data from the Basic Health Research in 2018, with the most proportion of anemia found in the 15-24 and 24-34 age groups. These cases clearly confirms that the health state of adolescents highly determines the success of health development, especially in the effort to establish the quality of the next generation in the future. This research uses case control design, where the case group population are students at Muhammadiyah Elementary Schools located in the city of Samarinda, East Kalimantan Province, whereas the control group population are students from Islamic Elementary Schools in the city of Samarinda, East Kalimantan Province. The statistic analysis being used is the multiple regression analysis to look for risk factor with the highest effect. This is a retrospective research, that is extracting past variable information from respondents so recall bias, which can cause wrong information, is at risk of occurance. Furthermore, the bias that might occur is that the respondent is bias by giving false answers. Another mistake is in the form of other cofounding variables not included in the research, which results in risk estimation value error.